Spatial and Seasonal Patterns of Mercury Accumulation in Paddy Soil around Nam Son Landfill, Hanoi, Vietnam - Nguyen Thi Quynh; Huiho Jeong; Ahmed Elwaleed; Willy Cahya Nugraha; Koji Arizono; Tetsuro Agusa; Yasuhiro Ishibashi (Soil Systems, 2024)
Landfills have the potential to contribute to mercury (Hg) pollution, due to the burial of waste containing mercury. Mercury from domestic waste can enter the soil surrounding landfills through surface runoff and leachate. In this study, we assessed the levels of Hg in the paddy soil around the Nam Son landfill, the largest landfill in the North of Vietnam, during both rainy (September 2021) and dry (January 2022) seasons. The concentration of Hg was in the range of 20.5 to 79.7 μg/kg dry w.t. in Bac Son and Nam Son, and 16.6 μg/kg dry w.t. at a higher reference site. In most of the samples, the rainy season showed higher Hg concentrations than the dry season. Soil samples taken closer to the landfill exhibited higher levels of Hg contamination compared to those in more distant paddy areas, suggesting a decreasing trend of Hg concentration as one moves away from the pollution source. Additionally, Hg concentration was found to decrease vertically from the surface, with the higher value observed in the surface layer (0–5 cm), and the lower in the bottom layer (20–25 cm). The geo-accumulation index showed that all the sampling points were moderately to heavily polluted, indicating that Hg was lost from the waste source in the landfill. This study provides valuable insights into the spatial and vertical distribution of Hg pollution in the topsoil and highlights the importance of managing and assessing the risks of Hg-containing waste.